Use of natural emulsifiers in model coffee creamers: Physical properties of quillaja saponin-stabilized emulsions. (June 2017) - Chung, Cheryl; Sher, Alexander; Rousset, Philippe; McClements, David Julian
Abstract: Consumer demands for natural and clean label ingredients is promoting food and beverage manufacturers to replace synthetic emulsifiers with natural alternatives. This study examined the potential use of quillaja saponin (Q-Naturale 200 ® ) as a natural emulsifier in model coffee creamers. The model liquid creamer was an oil-in-water emulsion (2% quillaja saponin, 10% medium chain triglycerides) that had a whitish milk color (lightness, L*  = 86–90) similar to a commercial liquid creamer ( L*  = 91–93). The model creamer was stable to droplet aggregation and creaming from pH 3.5 to 7.0, which was attributed to the small droplet diameter ( d  < 0.2 μm) and high droplet charge (ζ-potential = −20 to −50 mV). Addition of model creamer to hot black coffee (85 °C) at varying coffee concentrations (0.85–1.7%) and fat content (0–1.5%) produced white coffee drinks that had similar visual appearance and tristimulus color coordinates as those produced by a commercial creamer. No feathering was observed in the model white coffee systems, which indicated that the model creamer was stable after addition to hot coffee solutions. Addition of sugar (1 or 2 g) to the coffee followed by creamer addition had no effect on the stability of the white coffee drinks. Overall, the information obtained has useful implications for the use of natural emulsifiers in place of synthetic ones in food and beverage applications. Graphical abstract: Highlights: Creamers are added to coffee to give appearance, flavor and mouthfeel. Plant-based model creamers similar to milk-based creamers were fabricated. Quillaja saponin-stabilized creamers have high stability to pH and heating.